2022
DOI: 10.1155/2022/2184867
|View full text |Cite|
|
Sign up to set email alerts
|

The Higher Expression of CDCA2 Associated with Poor Prognosis in Glioma

Abstract: Glioma is the most common primary intracranial tumor and is related to poor clinical outcomes. The developments of sensitive markers can be applied to reveal the mechanisms involved in the progression of glioma. This study examined CDCA2 expression in glioma samples and its significance in predicting glioma patient outcome. GEPIA and GEO datasets were used to explore the expression of CDCA2 in glioma. Kaplan-Meier and multivariate assays were applied to delve into the prognostic values of CDCA2 expression in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, the gene expression of IRAG1 was upregulated in the context of pancreatic ductal adenocarcinoma (PDAC) after silencing the transcription factor basic transcription factor 3 (BTF3) in pancreatic cancer cell lines [ 46 ]. Additionally, expression of IRAG1 was negatively associated with high expression of the cell division cycle-associated protein 2 (CDCA2) in glioma [ 47 ].…”
Section: Functional Features Of Irag1mentioning
confidence: 99%
“…Furthermore, the gene expression of IRAG1 was upregulated in the context of pancreatic ductal adenocarcinoma (PDAC) after silencing the transcription factor basic transcription factor 3 (BTF3) in pancreatic cancer cell lines [ 46 ]. Additionally, expression of IRAG1 was negatively associated with high expression of the cell division cycle-associated protein 2 (CDCA2) in glioma [ 47 ].…”
Section: Functional Features Of Irag1mentioning
confidence: 99%
“…Currently, studies have shown that the subunits of condensin, such as NCAPG, SMC4, and NCAPG2, have been reported to be involved in the glioma pathogenesis. Wherein, NCAPG could be positively related to CDCA2 (cell division cycle-associated protein 2) in glioma, and the over-expression of NCAPG may regulate the cell cycle and promote the proliferation, migration, and invasion of glioma cells (Liang et al, 2016 ; Jiang et al, 2022 ; Jin et al, 2022 ). Meanwhile, NCAPG overexpression can also increase the expression of MHCI and AMAD17 molecules, both of which are located on the tumor surface, thus, assisting in camouflaging the tumor and preventing NK cells from being activated in the immune microenvironment (Zheng et al, 2022 ).…”
Section: Condensin and Nervous System Tumorsmentioning
confidence: 99%
“…From 2016, when the World Health Organization combined histopathology and molecular features for the rst time in the classi cation of central nervous system tumors, to 2021, the classi cation of glioma was continuously modi ed according to histopathology and molecular features, marking an important shift in glioma classi cation [19]. More and more researches focus on molecular biomarkers to aid in glioma diagnosis and treatment [20,21]. ANXA5 is an annexin with high a nity for phosphatidylserine through calcium ion.…”
Section: Y15 Could Reverse the Promoting Effect Of Anxa5 On Glioma Cellsmentioning
confidence: 99%